Changes in microbial community diversity, composition, and functions upon nitrate and Cr(VI) contaminated groundwater. (February 2022) - Hu, Yutian; Liu, Tong; Chen, Nan; Feng, Chuanping
Abstract: With the increasing occurrences of nitrate and Cr(VI) pollution globally, microbially driven pollutant reduction and its interaction effects were of growing interest. Despite the increasing number of experimental reports on the simultaneous reduction of nitrate and Cr(VI), a broad picture of the keystone species and metabolic differences in this process remained elusive. This study explored the changing of microorganisms with the introduction of Cr(VI)/NO3 − through analyzing 242 samples from the NCBI database. The correlation between microbial abundance and environmental factors showed that, the types of energy substances and pollutants species in the environment had an impact on the diversity of microorganisms and community structure. The genus of Zoogloea, Candidatus Accumulibacter, and Candidatus Kapabacteria sp. 59–99 had the ability of denitrification, while genus of Alcaligenes, Kerstersia, Petrimonas, and Leucobacter showed effectively Cr(VI) resistance and reducing ability. Azoarcus, Pseudomonas, and Thauera were recognized as important candidates in the simultaneous reduction of nitrate and Cr(VI). Metagenomic predictions of these microorganisms using PICRUSt2 further highlighted the enrichment of Cr(VI)and nitrate reduction-related genes (such as chrA and norC). Special attention should therefore be paid to these bacteria in subsequent studies to evaluate their performance and mechanisms involved in simultaneous denitrification and chromium removal. The microbial co-occurrence network analysis conducted on this basis emphasized a strong association between community collaboration and pollution removal. Collectively, either site surveys or laboratory experiments, subsequent studies should focus on these microbial populations and the interspecific collaborations as they strongly influence the occurrence of simultaneous nitrate and Cr(VI) reduction. Graphical abstract: Image 1 Highlights: Microbial diversity was related to the types and concentrations of contaminants. Energy sources and electron acceptors cause Discrepant bacteria at genus level. NO3 − -Cr(VI) reduction was the results of varieties of microbial cooperation actions. Non-random co-occurrence and functional driven modular patterns were exhibited. The major functional genes and the metabolism patterns were explored.